PERIPHERAL NERVE BLOCK OF THE FOOT – UTILITY IN DERMATOLOGIC SURGERY - Teixeira, Vera; Cabral, Rita; Vieira, Ricardo; Figueiredo, Américo (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Introduction: Skin cancer of the feet require quick surgical management with the less as possible organic impact, especially in elderly patients with multiple comorbidities. The techniques of regional block anesthesia are relatively easy to perform and safe when performed rigorously. Discussion: The sensitive innervation of the feet depends on five nervous branches: posterior tibial nerve, deep peroneal nerve, superficial peroneal nerve, sural nerve and saphenous nerve. The authors discuss the anesthesia techniques and possible complications. Conclusions: The techniques of anesthesia of peripheral nerves of the feet can achieve success rates of 95% and optimize the resources available in dermatologic surgery. KEYWORDS – Nerve Block; Peripheral Nerves; Foot; Skin Diseases.